2021
DOI: 10.3390/agronomy11020302
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Effects of Crop Residue Management on Soil Quality and Crop Production under Different Soil Management Regimes in Corn-Wheat Rotation Systems

Abstract: Strategic management of crop residues is essential to enhance soil quality for sustainable agriculture. However, little is known about the specific amounts of crop residues needed to improve soil quality characteristics which are key to develop economic plans. In this study, we investigated the effects of applying crop residue at five rates, including 100% (R100), 75% (R75), 50% (R50), 25% (R25), and 0% (R0), on wheat yield and soil properties. Field experiments were conducted for two cropping seasons in a whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 107 publications
1
24
0
Order By: Relevance
“…Amongst the TRS management practices, it was observed that uptake of Zn, Fe and Mn was found higher under ZTW+R followed by CTW-R followed by ZTW-R. The retention of crop residue might have increased the soil organic matter which resulted in increased micronutrients solubility and availability for plant uptake by forming chelates [30]. Thus, incorporation of organic residue along with the retention of soil structure with least disturbances enhanced the micronutrient availability to crop which resulted in higher micronutrient uptake by plants.…”
Section: Removal Of Micronutrients (Zn Cu Fe and Mn) By Rice Grain And Strawmentioning
confidence: 99%
“…Amongst the TRS management practices, it was observed that uptake of Zn, Fe and Mn was found higher under ZTW+R followed by CTW-R followed by ZTW-R. The retention of crop residue might have increased the soil organic matter which resulted in increased micronutrients solubility and availability for plant uptake by forming chelates [30]. Thus, incorporation of organic residue along with the retention of soil structure with least disturbances enhanced the micronutrient availability to crop which resulted in higher micronutrient uptake by plants.…”
Section: Removal Of Micronutrients (Zn Cu Fe and Mn) By Rice Grain And Strawmentioning
confidence: 99%
“…Furthermore, several studies have suggested that retaining a moderate quantity (50%) of crop residues can increase crop productivity. Under irrigated conditions, a short-term evaluation of applying crop residue at different rates (ranging from 25 to 100%) and with varied tillage techniques showed that applying residues at R100, followed by R75 and R50, significantly enhanced soil organic carbon and wheat grain production (Mirzaei et al, 2021. The benefits of reduced tillage practices can be more productive if optimally combined with crop residue management and mixedcropping systems (crop rotation diversification).…”
Section: Introductionmentioning
confidence: 99%
“…In Iran, the cultivation area of silage crops was about 280,000 ha with an average yield of 70 t ha −1 (Ministry of Jihad-e-Agriculture of Iran, 2018 ). Nowadays, this country is being affected by numerous land degradation processes in cultivated areas such as erosion, soil pollution, and loss of biodiversity due to non-sustainable land management practices such as intensive tillage operations, removal and burning of crop residues, monocropping, excessive use of chemical fertilizers, and lack of using green manures/cover crops (Sadeghi et al, 2008 ; Nawaz et al, 2017 ; Minaei et al, 2018 ; Javidan et al, 2019 ; Mirzaei et al, 2021 ; Mohammed et al, 2022 ; Eskandari Dameneh et al, 2021 ; Rodrigo-Comino et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 75% of this amount can be attributed to cereals (Bhattacharyya & Barman, 2018 ). Crop residues are removed from the field after harvest in many parts of the world (Cherubin et al, 2018 ; Kenney et al, 2015 ; Mirzaei et al, 2021 ; Turmel et al, 2015 ; Wegner et al, 2015 ; Wilhelm et al, 2004 ). The removed residues are generally used for food and fiber (animal feed and bedding, biofuel production, building materials, household fuel, paper making, and mushroom cultivation), which adversely affect soil fertility, agronomic productivity, and environmental quality (Maw et al, 2019 ; Mirzaei et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation